Crónica de un fallo : El concurso del Museo del Prado - Fernandez-Galiano, Luis (1996)
Proyectos de <Matos-Martínez Castillo>, <Dürig - Rämi>, Moneo, Pardo,<Arana-Arana-Aroca-Población>, <Hernández Gil-Olaquiaga>, Marco,<Barrionuevo-Molino-Daroca>, Zoido, Govela
Keywords: MATOS CASTANO, BEATRIZ; MARTÍNEZ CASTILLO, ALBERTO; CONCURSOS; ARQUITECTURA; ESPAÑA; MUSEOS DE ARTE; RENOVACION URBANA; MUSEOS